TRANSFORMASI TEKNOLOGI INFORMASI DALAM MENDUKUNG PROSES PEMILIHAN KEPADA DAERAH YANG DEMOKRATIS - Mardani, Retno Eko; Nugraha, Satriya (PSHPM Untag Semarang, 2025)
Regional Head Elections are one of the main pillars of democracy in Indonesia. A fair, transparent, and efficient regional election process is very important to ensure legitimacy and public trust in the results of general elections because currently the election process is often considered not transparent so that the results are considered less than satisfactory. Therefore, innovation and breakthroughs are needed that can support the regional election process, which can increase the number of people participating in casting their votes, and the results can be received as well as possible. Information technology (IT) has great potential in supporting the implementation of democratic regional elections by improving various aspects, starting from voter registration, including updating the voter list, to the final stage of vote counting. This study aims to explore how information technology can be used to support democratic regional elections. The main focus of this study is on the identification and analysis of technology that can increase transparency, accountability, public participation, and security of the regional election process. This research method uses a qualitative approach with a literature review method. Data was collected from various sources, including scientific journals, news articles, and comparative studies of IT implementation in elections in various countries.